Impact of delay in cystoscopic surveillance on recurrence and progression rates in patients with non‐muscle‐invasive bladder cancer during the COVID‐19 pandemic. Issue 9 (22nd June 2021) - Culpan, Meftun; Keser, Ferhat; Acar, Hazal Cansu; Otunctemur, Alper; Kucuk, Eyup Veli; Erdem, Selcuk; Ozer, Murat; Sen, Ugur Tolga; Degirmenci, Enes; Ergul, Rifat; Atis, Ramazan Gokhan; Yildirim, Asif
Abstract: Purpose: To evaluate the impact of delay in cystoscopic surveillance on recurrence and progression rates in non‐muscle‐invasive bladder cancer (NMIBC). Materials and methods: A total of 407 patients from four high‐volume centres with NMIBC that applied for follow‐up cystoscopy were included in our study prospectively. Patients' demographics and previous tumour characteristics, the presence of tumour in follow‐up cystoscopy, the pathology results of the latest transurethral resection of bladder tumour (if tumour was detected) and the delay in cystoscopy time were recorded. Our primary outcomes were tumour recurrences detected by follow‐up cystoscopy and progression. Multivariate logistic regression analysis was performed using the possible factors identified with univariate analyses ( P values ≤ .2). Results: A total of 105 patients (25.8%) had tumour recurrence in follow‐up cystoscopy, and 20 (5.1%) of these patients had disease progression according to grade or stage. In multivariate analysis, the number of recurrences (OR: 1.307, P  < .001) and the cystoscopy delay time (62‐147 days, OR: 2.424, P  = .002; >147 days, OR: 4.883, P  < .001) were significant risk factors for tumour recurrence on follow‐up cystoscopy; the number of recurrences (OR: 1.255, P  = .024) and cystoscopy delay time (>90 days, OR: 6.704, P  = .002) were significant risk factors for tumour progression. Conclusions: This study showed that a 2‐5 months of delay in follow‐up cystoscopy increases the risk of recurrence by 2.4‐fold, and delay in cystoscopy for more than 3 months increases the probability of progression by 6.7‐fold. We suggest that cystoscopic surveillance should be done during the COVID‐19 pandemic according to the schedule set by relevant guidelines.